PENGGUNAAN METODE BELAJAR PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR DAN KEMAMPUAN KOLABORASI MATERI DIAGRAM PADA SISWA KELAS 5 SEKOLAH DASAR - Yunastiti Primanda Hapsari; Pujiati; Agustina Ika Widya Gunita (STKIP Subang, 2024)
Education is a vital aspect in building a nation, especially in shaping the character and skills of young generations. In Indonesia, the quality of education still faces various challenges, despite continuous efforts to improve it. Effective teaching methods significantly impact students' learning outcomes, one of which is the Problem-Based Learning (PBL) method. This method allows students to work collaboratively in solving problems, helping them not only to understand the material but also to enhance critical thinking and teamwork skills. This research aims to explore the application of the PBL method in teaching diagrams to 5th-grade elementary students and how it can improve their collaborative skills and learning outcomes. The research method used is classroom action research with a qualitative approach. The study was conducted at SDN 02 Demangan, Madiun City, involving two teaching cycles. The results showed a significant improvement in students' learning outcomes, with a mastery level of 85.2% in the second cycle. Moreover, students' collaborative abilities also improved, as evidenced by observations and questionnaires conducted during the learning process. In conclusion, the implementation of PBL can enhance both learning outcomes and collaboration skills, especially in diagram-related topics. This method effectively engages students in active learning, which is essential for developing 21st-century skills such as teamwork and critical thinking